The Relationship Between a Firm's Level of Technological Innovativeness and Its Pattern of Partnership Agreements - Dutta, Shantanu; Weiss, Allen M. (Management Science, 1997)
In this paper we investigate the relationship between the level of a firm's technological innovativeness and its pattern of partnership agreements (i.e., relative number of partnership agreements of one type versus another). We argue that the protection of tacit technological knowledge from potential opportunism is of importance to technologically innovative firms, and as a result they tend to have a relatively larger number of partnership agreements which generally minimize the transfer of tacit technological knowledge. Specifically, they tend to have a greater number of marketing agreements than joint ventures and a greater number of licensing agreements than joint ventures. This argument is tested using data from manufacturing firms in the electrical and electronics machinery sector who invest in R&D, and our results hold for our focal firm's agreements with both domestic and foreign partners. We discuss the strategic and policy implications from this research. In particular, the empirical results suggest that technologically innovative firms already have relatively more agreements which are likely to preempt transfer of their tacit technological knowledge to their foreign partners. Thus, recent suggestions of more active government regulation in the area of intellectual property may be unwarranted.